Assessment of the Inferior Mandibular Canal’s Position by Cone-Beam Computed Tomography - Aghdasi, Mohammad Mehdi; Sheikhdavodi, Nima; Moshfeghi, Mahkameh; Asna ashari, Mohammad (Journal of Dental School, 2019)
Objectives: It is important to know the exact location and anatomic variety of inferior alveolar nerve canal for different procedures of mandibular surgeries. The aim of the present study was to evaluate inferior mandibular canal’s anatomic position by Cone-beam Computed Tomography (CBCT). Methods: In a cross sectional study, CBCT were taken and assessed from 130 patients (260 semi-arch) referring to the radiologic department of Shahid Beheshti Dental Faculty. Three points including 1cm before mental foramen (point A), under second molar’s furcation (point B) and 1cm after mandibular foramen on the inferior alveolar canal (point C) were chosen. The canal diameter, length and the distance between the canal and inferior border of mandible were measured. SPSS version 19 software used for data analysis. T and variance tests evaluated the role of age, gender, canal length and jaw side. Results: Mean age of patients was 43.73±13.25. Canal length, 61.71 ± 4.95 ml and canal diameter was 2.94 ± 0.58 mm. The distance between the canal and the inferior border of mandible was 9.47 ± 2.23 mm. There was a significant difference in gender and age for all parameters. The distance between the canal and the inferior border in C point and at mental foramen in cases with short and long canal length showed a significant difference. (p≤0.012) None of the variables showed significant difference between right and left sides. Conclusion: The anatomic position of mandibular canal is related to gender and canal length, and independent to age and side.